Vasodilatory Effect of the Dissolved Glycine locally applied on Pial Microvessels - Tyukina ES; Sheshegova EV; Nartsissov YR; Podoprigora GI (Annals of Circulation - Peertechz Publications, 2017)
By the method of biomicroscopy it was shown that a single application of a dissolved glycine on the parietal region of the rat brain ("open window" technique) leads to a vasodilatation - an increase in arteriolar diameter about 1.5-2 times. There were no changes in the microcirculation when saline applied under similar conditions. It was also shown that there were no pH effects on the microvessels. For the testing of the vasodilatory effect of glycine in arteriol spastic conditions the adrenomimetic phenylephrine hydrochloride possessing the vasoconstrictor properties has been used as an agent for ischemic stroke modeling. Further work on the development of an adequate ischemic stroke models is the prospective task for the testing of antiischemic preparations.